2016
DOI: 10.26226/morressier.5785edcfd462b80296c99eca
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Glutamate-modulating drugs as a potential therapeutic strategy in obsessive-compulsive disorder

Abstract: Objective: Obsessive-compulsive disorder (OCD) is a mental disease commonly associated with severe distress and impairment of social functioning. Serotonin reuptake inhibitors and/or cognitive behavioural therapy are the therapy of choice, however up to 40% of patients do not respond to treatment. Glutamatergic signalling has also been implicated in OCD. The aim of the current study was to review the clinical evidence for therapeutic utility of glutamate-modulating drugs as an augmentation or monotherapy in OC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 77 publications
0
3
0
1
Order By: Relevance
“…Another system probably involved in OCD is the glutamatergic system. The glutamate-modulating drugs have recently been investigated as potentially new treatment targets for this disorder (Marazziti et al, 2018; Marinova et al, 2017; Pittenger et al, 2011; Rajendram et al, 2017). Since 5-HT 3 receptor antagonists have glutamate modulating effects through antagonizing inhibitory effects of 5-HT 3 receptors on N-methyl-d-aspartate (NMDA) receptors, they could exert their obsession and compulsion attenuating properties in this pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Another system probably involved in OCD is the glutamatergic system. The glutamate-modulating drugs have recently been investigated as potentially new treatment targets for this disorder (Marazziti et al, 2018; Marinova et al, 2017; Pittenger et al, 2011; Rajendram et al, 2017). Since 5-HT 3 receptor antagonists have glutamate modulating effects through antagonizing inhibitory effects of 5-HT 3 receptors on N-methyl-d-aspartate (NMDA) receptors, they could exert their obsession and compulsion attenuating properties in this pathway.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis found that memantine showed positive effects as an augmentation therapy in OCD (Modarresi, Chaibakhsh, Koulaeinejad, & Koupaei, 2019). Moreover, glutamatergic anticonvulsant drugs (lamotrigine and topiramate) and riluzole may provide therapeutic benefits to some OCD patients (Marinova, Chuang, & Fineberg, 2017). Ketamine, an N -methyl- d -aspartate receptor antagonist, may also be of interest due to its potential for a rapid onset of action, but further randomized placebo-controlled trials in larger study populations are necessary to draw definitive conclusions.…”
Section: Clinical and Therapeutic Implicationsmentioning
confidence: 99%
“…3 Based on this premise, signs of FHS should diminish and/or disappear after initiation of behaviour modification and/or treatment with psychoactive medications such as selective serotonin reuptake inhibitors (SSRIs; eg, fluoxetine) or tricyclic antidepressants (eg, clomipramine or amitriptyline), and glutamate-modulating medications (eg, topiramate and gabapentin) (see Figure 2). 3,8 Although in some cases this therapeutic approach might be satisfactory, in our study 2/4 cats achieved remission of clinical signs only after anti-inflammatory or immunosuppressive medications were added to psychotropic drugs.…”
Section: Discussionmentioning
confidence: 50%